PENGARUH ORDE BARU TERHADAP NARASI FILM HIBURAN DAN KEPENONTONAN DI INDONESIA SELAMA TAHUN 2016 - Banjaransari, Tunggul (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
It has been 18 years The New Order didn’t exist anymore. But they still have a lot of impact on film and the audience. That impact happens on film beraucrat including distribution film and association of film worker, until method of film production including content story and the context. There are many changes on the influences of New Order. The influences isn’t always happen on verbal content like heroism film, collosal film, and political film, but also sneaking into drama film, teenager film, and also comedy film which is that film didn’t tell anything about political content, or the film that considered purely entertainment or commercial film. That’s become point of view of this article, using material content of drama, comedy, and teenager film to find the context of the New Order influences. There is some effort to planting New Order mind into the generation after 1998, while this regime treated and reconstructed some historical data according to their own truth, muffled freedom of expression on art (incuding film), and anti criticized.